Oil palm plantation mechanisation in totality - El Pebrian, Darius; Yahya, Azmi; Ishola, Tajudeen Abiodun; Roodi, Siamak Moslehi; Hasan, Haslina (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Scarcities of labour and low labour productivity are seen to be the unending characters in the oil palm plantation industry in Malaysia. The two characters could be regarded as the pertinent push factors for an holistic implementation of a sustainable mechanisation programme in the oil palm plantation. A complete machinery package that adopts the concept of mechanisation in-totality has been designed, developed and evaluated to offer a solution to the problems. The package consists of a universal single chassis, 4WD, 4WS prime mover with selectable and easily mounted machine attachments for soil filling in polybags, seedling transplanting, VRT band fertilising, herbicide circle spraying, herbicide blanket spraying, and in-field fresh fruit bunch (FFB) collection-transportation. The prime mover design was such as to allow better control and comfort to the operator under the harsh field environment and at the same time give greater maneuverability and stability to the overall machine system under the rugged terrain condition. Good feature with the machine system is that the units are self-propelled and self-contained, completely integrated having a continuous once-over-operation, simple in construction and operation and at the same time economical and reliable to be adopted. This new and innovative technology has great potential in maintaining the country’s oil palm industry competitive edge through alleviation of labor shortage and enhancement of labor productivity.